Categorizing Fetal Heart Rate Variability with and without Visual Aids. (September 2015) - Ashdown, Amanda J.; Scerbo, Mark W.; Belfore, Lee A.; Abuhamad, Alfred Z.; Davis, Stephen S.
The present study examined the ability to categorize fetal heart rate (FHR) variability with and without the use of visual aids. Participants were instructed to categorize examples of FHR images into four categories of variability defined by the National Institute of Child Health and Human Development: absent, minimal, moderate, or marked. Participants took part in three visual aid conditions: prototypical aids, nonprototypical aids, and no visual aids. Each participant was required to categorize examples of prototypical and nonprototypical FHR images in each of the four categories of variability. The results showed that participants responded faster to and correctly categorized more prototypical FHR images compared to nonprototypical images. Moreover, the use of prototypical and nonprototypical visual aids significantly improved participants' performance in categorizing the FHR images. These results suggest that an alignable, high similarity visual aid can improve the ability to correctly categorizing FHR variability and could potential improve the ability of clinicians to determine fetal health during labor.